Remote Working and TOGAF: Architecture Vision - Harias Kalbuadi; Alfa Ryano Yohanis (Eduvest - Journal of Universal Studies, 2024)
The COVID-19 pandemic, which implements social distancing, has led to the emergence of new habits in carrying out work with remote working models such as WFA (Work from Anywhere) or WFH (Work from Home). Challenges in implementing remote working, both from the human resources and technology aspects, require adaptation processes. How an organization prepares its IT enterprise architecture to support the WFA process to run smoothly is crucial. On the other hand, limitations in resources and organizational focus will influence decisions in determining which technologies will be used and implemented in the organization and what obstacles may arise in the implementation of WFA and what new technologies the organization will use, whether they will use open source or internal source starting from the process of developing new systems.